2013
DOI: 10.1093/applin/amt042
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical Research Article as a Reflection of Disciplinary Practices: The Case of Pure Mathematics

Abstract: Recent years have seen an interest in the generic structure of empirical research articles across a variety of disciplines. However, significantly less attention has been given to theoretical articles. This study aims to begin to address this imbalance by presenting the results of an investigation into the organizational and rhetorical structure of theoretical pure mathematics research articles. The data set combines a close analysis of 22 peer-reviewed articles and semi-structured interviews with their author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Table 4 or Table 5 because they were observed in only one article. The researcher told us that this particular study was mathematically oriented which is reported to utilize a unique rhetorical structure (Anthony and Bowen, 2013;Kuteeva and McGrath, 2013).…”
Section: Move 7: Reporting Resultsmentioning
confidence: 99%
“…Table 4 or Table 5 because they were observed in only one article. The researcher told us that this particular study was mathematically oriented which is reported to utilize a unique rhetorical structure (Anthony and Bowen, 2013;Kuteeva and McGrath, 2013).…”
Section: Move 7: Reporting Resultsmentioning
confidence: 99%
“…Other studies of disciplinary discourses in ESP have been largely corpus-based and focused on specific genres and move structures (e.g. Huckin, 2001;Kuteeva & McGrath, 2015;Lin & Evans, 2012;Yang & Allison, 2004) or syntactic and lexical features (e.g. Hewings & Hewings, 2001;Hyland, 1999Hyland, , 2008McGrath & Kuteeva, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To exemplify how these functions are represented in text, the second move often involves the authors identifying what type of research is missing or incomplete within the discipline and, in the third move, the authors introduce their own research and how it, in one way or another, addresses what is regarded to be missing. As an extension of Swales' work, numerous scholars have developed discipline-specific moves analyses for various disciplines, for example computer science (Posteguillo 1999), biochemistry (Kanoksilapatham 2005) and mathematics (Kuteeva and McGrath 2015). Although these studies do not aim specifically at pedagogical application, the pedagogical value of the developed framework tends to be stressed.…”
Section: Teaching and Learning Of Genre Writing In Science And Enginementioning
confidence: 99%